Predicting Severity and Intrahospital Mortality in COVID-19: The Place and Role of Oxidative Stress. (27th March 2021) - Cekerevac, Ivan; Turnic, Tamara Nikolic; Draginic, Nevena; Andjic, Marijana; Zivkovic, Vladimir; Simovic, Stefan; Susa, Romana; Novkovic, Ljiljana; Mijailovic, Zeljko; Andjelkovic, Marija; Vukicevic, Vladimir; Vulovic, Tatjana; et al.
Abstract : SARS-CoV-2 virus causes infection which led to a global pandemic in 2020 with the development of severe acute respiratory syndrome. Therefore, this study was aimed at examining its possible role in predicting severity and intrahospital mortality of COVID-19, alongside with other laboratory and biochemical procedures, clinical signs, symptoms, and comorbidity. This study, approved by the Ethical Committee of Clinical Center Kragujevac, was designed as an observational prospective cross-sectional clinical study which was conducted on 127 patients with diagnosed respiratory COVID-19 viral infection from April to August 2020. The primary goals were to determine the predictors of COVID-19 severity and to determine the predictors of the negative outcome of COVID-19 infection. All patients were divided into three categories: patients with a mild form, moderate form, and severe form of COVID-19 infection. All biochemical and laboratory procedures were done on the first day of the hospital admission. Respiratory (p < 0.001 ) and heart (p = 0.002 ) rates at admission were significantly higher in patients with a severe form of COVID-19. From all observed hematological and inflammatory markers, only white blood cell count (9.43 ± 4.62, p = 0.001 ) and LDH (643.13 ± 313.3, p = 0.002 ) were significantly higher in the severe COVID-19 group. We have observed that in the severe form of SARS-CoV-2, the levels of superoxide anion radicals were substantially higher than those in two other groups (11.3 ± 5.66, p < 0.001 ) and the nitric oxide level was significantly lower in patients with the severe disease (2.66 ± 0.45, p < 0.001 ). Using a linear regression model, TA, anosmia, ageusia, O2 −, and the duration at the ICU are estimated as predictors of severity of SARS-CoV-2 disease. The presence of dyspnea and a higher heart rate were confirmed as predictors of a negative, fatal outcome. Results from our study show that presence of hypertension, anosmia, and ageusia, as well as the duration of ICU stay, and serum levels of O2 − are predictors of COVID-19 severity, while the presence of dyspnea and an increased heart rate on admission were predictors of COVID-19 mortality.